Information Marketing Initiatives in Agriculture Related Special Libraries in Ghana - Kwadzo, G.; Amekuedee, J.O. (Ghana Library Journal, 2007)
The purpose of this paper is to explore the extent to which marketing principles are adopted in the provision of library services in agriculture related special libraries in Ghana. For this study, a questionnaire was used to collect data from librarians in charge of libraries. The study areas examined were level of training of library personnel, resources available to them for product design and marketing, and implementation of marketing principles. The study found out that libraries undertake limited marketing activities. Their activities are mostly promotional. These are newsletters, talks and exhibitions among others. The librarians have had some training in marketing through workshops and courses in the Department of Information Studies, University of Ghana, Legon. In spite of the above activities, none of the libraries had a marketing plan. They lacked adequate budget to support their activities. The library collections do not adequately meet the needs of the users due to its limitation in numbers, subject coverage and currency. The study concludes with recommendations that would enhance the marketing skills of the agriculture related special libraries.